Biomass-based hard carbon negative electrode material, preparation method thereof and sodium ion battery
By introducing ash remover and a coating agent in the preparation process of biomass-based hard carbon anode material, the problem of low capacity of hard carbon anode materials in the prior art is solved, and the capacity and circulation performance are improved.
Patent Information
- Application Number
- CN202411726076.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-18
AI Technical Summary
In the prior art, the hard carbon anode material prepared separately from biomass materials has a low capacity, which limits its application.
During the preparation process, ash removal agent and a coating agent are introduced to reduce the ash content in the hard carbon material by reacting with impurities in the biomass-based raw materials, and a protective film is formed on the hard carbon surface to improve circulation performance and rateability.
The capacity and first-term effect of hard carbon negative electrode materials are improved, their circulation performance and rate-based properties are enhanced, and the problem of low capacity is solved.
Smart Images

Figure VDTWT1CA3LTRSCNWFJGHHIC9ZNZFHTVIYKR3FBHA
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a biomass-based hard carbon negative electrode material and a preparation method thereof, and a sodium ion battery. Background Art
[0002] Due to the limited storage capacity and uneven distribution of lithium ions, the cost of lithium-ion batteries is relatively high, which limits their application in low-cost energy storage devices. At the same time, sodium-ion batteries have attracted much attention due to their low cost and high safety performance, and are expected to replace lithium-ion batteries.
[0003] As one of the main components of sodium-ion batteries, the negative electrode material has an important influence on the energy density and cycle life of sodium-ion batteries. Sodium and lithium are in the same main group and have similar physical and chemical properties. However, since the ionic radius of sodium ions is larger than that of lithium ions, the graphite negative electrode traditionally used in lithium-ion batteries is not suitable for sodium-ion batteries. Therefore, it is necessary to develop negative electrode materials suitable for sodium-ion batteries.
[0004] Among many sodium storage negative electrode materials, hard carbon materials have become the most promising negative electrode materials for sodium ion batteries due to their large interlayer space. At present, biomass materials are mainly used as carbon source precursors in the preparation of hard carbon negative electrode materials. However, the hard carbon negative electrode materials prepared directly from biomass materials have low capacity, which limits the application of biomass-based hard carbon negative electrode materials. Summary of the invention
[0005] In order to solve the problem of low capacity of hard carbon negative electrode materials prepared solely with biomass materials in the prior art, the present invention provides a method for preparing biomass-based hard carbon negative electrode materials. By introducing a dust removal agent and a coating agent during the preparation process, the capacity of the hard carbon negative electrode material is improved while the cycle performance and rate capability are improved, thereby solving the problem of low capacity of hard carbon negative electrode materials prepared solely with biomass materials in the prior art.
[0006] The technical solution adopted by the present invention to solve its technical problem is: A method for preparing a biomass-based hard carbon negative electrode material comprises the following steps: S1: mixing a biomass raw material, a ash removal agent and a solvent to obtain a mixed solution; S2: After the mixed solution is allowed to stand at 25° C.-120° C., it is washed and dried to obtain a mixed material; S3: coating the mixed material with a coating agent to obtain a coated material; S4: In an inert gas atmosphere, the coated material is kept at 200-400° C. to obtain an intermediate product; S5: In an inert gas atmosphere, the intermediate product is kept at 1200-1700° C. to obtain a biomass-based hard carbon negative electrode material.
[0007] Optionally, the biomass raw material is selected from at least one of bagasse, bamboo charcoal, coffee grounds and straw residues.
[0008] Optionally, the deashing agent includes an organic phosphonate deashing agent and a polyacrylic acid deashing agent.
[0009] Optionally, the organic phosphonate deashing agent is selected from at least one of tetrasodium hydroxyethylene diphosphonate, sodium ethylenediamine tetramethylene phosphate, diethylenetriamine penta (methylene phosphonate), and amine trimethylene phosphate.
[0010] Optionally, the polyacrylic acid deashing agent is selected from at least one of hydrolyzed polymaleic anhydride, polyacrylic acid, polyhydroxyacrylic acid, maleic acid acrylic acid copolymer, and polyacrylamide.
[0011] Optionally, the mass ratio of the organic phosphonate deashing agent to the polyacrylic acid deashing agent is (100-1): (1-100).
[0012] Optionally, the coating agent is selected from at least one of petroleum asphalt, coal tar, sucrose, starch, sucrose, fructose, phenolic resin, epoxy resin, polydopamine, polyvinyl pyrrolidone, tannic acid, citric acid, polyvinyl alcohol, polypyrrole, vitamin C, polyethylene glycol, and aniline.
[0013] Optionally, in step S1, the mass ratio of the biomass raw material to the ash removal agent is (5-500):1; and in step S3, the mass ratio of the mixed material to the coating agent is (50-500):1.
[0014] Another object of the present invention is to provide a biomass-based hard carbon negative electrode material, which is prepared by the method for preparing the biomass-based hard carbon negative electrode material as described above.
[0015] Another object of the present invention is to provide a sodium ion battery comprising the biomass-based hard carbon negative electrode material as described above.
[0016] The beneficial effects of the present invention are: The preparation method of the biomass-based hard carbon negative electrode material provided by the present invention, during the preparation process, uses a ash remover to react with impurities in the biomass-based raw material, thereby reducing the ash content in the hard carbon material and improving its capacity and initial efficiency; at the same time, through the coating step, a protective film can be formed on the hard carbon surface to avoid side reactions between the negative electrode material and the electrolyte during the cycle, thereby improving the cycle performance. DETAILED DESCRIPTION
[0017] The present invention is now further described in detail. The embodiments described below are exemplary and intended to be used to explain the present invention, but cannot be understood as limiting the present invention. All other embodiments obtained by ordinary technicians in this field without creative work based on the embodiments of the present invention belong to the scope of protection of the present invention.
[0018] In order to solve the problem of low capacity of hard carbon negative electrode materials prepared solely from biomass materials in the prior art, the present invention provides a method for preparing a biomass-based hard carbon negative electrode material, the preparation method comprising the following steps: S1: mixing a biomass raw material, a ash removal agent and a solvent to obtain a mixed solution; S2: After the mixed solution is allowed to stand at 25°C-120°C, it is washed and dried to obtain a mixed material; In this step, the mixed solution can be left standing at room temperature or under heating conditions, and the preferred standing time is 12 hours; S3: coating the mixed material with a coating agent to obtain a coated material; In this step, the coating can be carried out by dry mixing, such as ball milling, jar milling, high mixing, or by spraying the coating agent at high temperature under stirring; S4: In an inert gas atmosphere, the coated material is kept at 200-400° C. to obtain an intermediate product; Preferably, in this step, the coated material is heated to 200-400°C at 2°C / min, and further preferably to 300°C, and kept warm for 2 hours to obtain an intermediate product; through this step, the volatile matter in the biomass raw material and the coating agent is removed, and the mechanical strength and pore structure of the hard carbon are regulated; S5: In an inert gas atmosphere, the intermediate product is kept at 1200-1700° C. to obtain a biomass-based hard carbon negative electrode material; Preferably, in this step, the intermediate product is heated to 1200-1700° C. at a rate of 2° C. / min and kept at that temperature for 1-5 hours.
[0019] The preparation method of the biomass-based hard carbon negative electrode material provided by the present invention, during the preparation process, uses a ash remover to react with impurities in the biomass-based raw material, thereby reducing the ash content in the hard carbon material and improving its capacity and initial efficiency; at the same time, through the coating step, a protective film can be formed on the hard carbon surface to avoid side reactions between the negative electrode material and the electrolyte during the cycle, thereby improving the cycle performance.
[0020] The preferred biomass raw material of the present invention is biomass waste residue, and the preferred biomass raw material is at least one selected from bagasse, bamboo charcoal, coffee residue, and straw residue; further, the preferred biomass raw material has a particle size of 5-10 μm.
[0021] The present invention uses biomass waste residue as biomass raw material to prepare hard carbon negative electrode material, which has low cost and good environmental protection. However, the ash content in these biomass waste residues is relatively high. Directly preparing hard carbon negative electrode materials will result in a lower capacity of the hard carbon negative electrode material, and metal impurities in the negative electrode material are easily precipitated during the cycle, leading to safety problems such as short circuit of the battery cell. At present, in the preparation process of hard carbon negative electrode materials, the raw materials are usually removed by acid washing. This method is not only complicated to operate, but also inevitably produces a large amount of wastewater, which is not conducive to environmental protection. The present invention introduces a deashing agent to react with metal impurities such as iron, copper, calcium, magnesium, etc. in biomass waste residues to reduce the ash content of hard carbon, which is beneficial to reduce wastewater discharge and improve environmental protection while improving specific capacity and first efficiency.
[0022] In the present invention, the solvent in step S1 is preferably water.
[0023] In order to reduce the ash content in the hard carbon material to the greatest extent, the preferred deashing agent of the present invention is a composite deashing agent. Specifically, the preferred deashing agent includes an organic phosphonate deashing agent and a polyacrylic acid deashing agent.
[0024] Among them, organic phosphonate ash removers can form stable complexes with metal ions in biomass waste residues, while polyacrylic acid ash removers not only have the function of adsorbing impurities in biomass waste residues, but also have good colloidal properties and dispersion effects. By using organic phosphonate ash removers and polyacrylic acid ash removers in combination, it not only helps to remove ash in biomass precursors to the greatest extent, but also helps to improve the consistency of the performance of hard carbon negative electrode materials.
[0025] In the present invention, the organic phosphonate deashing agent is preferably selected from at least one of tetrasodium hydroxyethylene diphosphonate, sodium ethylenediaminetetramethylene phosphate, diethylenetriaminepenta(methylene phosphonate), and amine trimethylene phosphate; the polyacrylic acid deashing agent is preferably selected from at least one of hydrolyzed polymaleic anhydride, polyacrylic acid, polyhydroxyacrylic acid, maleic acid acrylic acid copolymer, and polyacrylamide; the mass ratio of the organic phosphonate deashing agent to the polyacrylic acid deashing agent is preferably (100-1): (1-100), and the mass ratio is further preferably 5:1.
[0026] In order to improve the rate performance of the hard carbon negative electrode material, the preferred coating agent of the present invention is selected from at least one of petroleum asphalt, coal tar, sucrose, starch, sucrose, fructose, phenolic resin, epoxy resin, polydopamine, polyvinyl pyrrolidone, tannic acid, citric acid, polyvinyl alcohol, polypyrrole, vitamin C, polyethylene glycol, and aniline.
[0027] On the one hand, the highly conductive coating agent can improve the conductivity of the material, which is beneficial to the improvement of the rate performance; on the other hand, a protective film can be formed on the hard carbon surface to avoid side reactions between the negative electrode material and the electrolyte during the cycle and improve the cycle performance.
[0028] In order to take into account both the electrochemical performance and the economy of the hard carbon negative electrode material, the mass ratio of the biomass raw material to the ash removal agent in step S1 of the present invention is preferably (5-500):1; the mass ratio of the mixed material to the coating agent in step S3 is (50-500):1.
[0029] Another object of the present invention is to provide a biomass-based hard carbon negative electrode material, which is prepared by the method for preparing the biomass-based hard carbon negative electrode material as described above.
[0030] The biomass-based hard carbon negative electrode material provided by the present invention uses a ash remover to react with impurities in the biomass-based raw material during the preparation process, thereby reducing the ash content in the hard carbon material and improving its capacity and initial efficiency; at the same time, through the coating step, a protective film can be formed on the hard carbon surface to avoid side reactions between the negative electrode material and the electrolyte during the cycle and improve the cycle performance.
[0031] Another object of the present invention is to provide a sodium ion battery, which comprises the biomass-based hard carbon negative electrode material as described above.
[0032] In the preparation process of the biomass-based hard carbon negative electrode material used in the sodium ion battery provided by the present invention, a ash remover is used to react with impurities in the biomass-based raw material, thereby reducing the ash content in the hard carbon material and improving its capacity and initial efficiency; at the same time, a protective film can be formed on the hard carbon surface through a coating step to avoid side reactions between the negative electrode material and the electrolyte during the cycle and improve the cycle performance.
[0033] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below.
[0034] Example 1 This embodiment provides a method for preparing a biomass-based hard carbon negative electrode material, comprising the following steps: S1: crushing and sieving bagasse to obtain a powder with a particle size of 5-10 μm; mixing the powder, a ash remover and water in a mass ratio of 250:1:100, stirring evenly to obtain a mixed solution; wherein the ash remover comprises tetrasodium hydroxyethylidene diphosphonate and polyhydroxyacrylic acid, and the mass ratio of tetrasodium hydroxyethylidene diphosphonate to polyhydroxyacrylic acid is 1:1; S2: heating the mixed solution to 80° C. and standing for 12 hours, washing, and drying to obtain a mixed material; S3: mixing the mixed material with petroleum asphalt in a mass ratio of 50:1, and ball milling to obtain a coated material; S4: Under a nitrogen atmosphere, the coated material was heated to 300°C at a rate of 2°C / min and kept at that temperature for 2h to obtain an intermediate product; S5: Under a nitrogen atmosphere, the intermediate product was heated to 1500°C at a rate of 2°C / min and carbonized for 3 h to obtain a biomass-based hard carbon negative electrode material.
[0035] Example 2 This embodiment provides a method for preparing a biomass-based hard carbon negative electrode material, comprising the following steps: S1: crushing bamboo charcoal, sieving, and obtaining a powder with a particle size of 5-10 μm; mixing the powder, a deashing agent, and water in a mass ratio of 300:1:100, and stirring evenly to obtain a mixed solution; wherein the deashing agent comprises tetrasodium hydroxyethylidene diphosphonate and polyhydroxyacrylic acid, and the mass ratio of tetrasodium hydroxyethylidene diphosphonate to polyhydroxyacrylic acid is 10:1; S2: The mixed solution is allowed to stand at room temperature for 12 hours, then washed and dried to obtain a mixed material; S3: mixing the mixed material with petroleum asphalt in a mass ratio of 80:1, and ball milling to obtain a coated material; S4: Under a nitrogen atmosphere, the coated material was heated to 300°C at a rate of 2°C / min and kept at that temperature for 2h to obtain an intermediate product; S5: Under a nitrogen atmosphere, the intermediate product was heated to 1200°C at a rate of 2°C / min and carbonized for 5 h to obtain a biomass-based hard carbon negative electrode material.
[0036] Example 3 This embodiment provides a method for preparing a biomass-based hard carbon negative electrode material, comprising the following steps: S1: Grind coffee grounds and sieve to obtain a powder with a particle size of 5-10 μm; mix the powder, a ash remover and water in a mass ratio of 400:1:100, stir evenly to obtain a mixed solution; wherein the ash remover comprises tetrasodium hydroxyethylidene diphosphonate and polyhydroxyacrylic acid, and the mass ratio of tetrasodium hydroxyethylidene diphosphonate to polyhydroxyacrylic acid is 30:1; S2: heating the mixed solution to 80° C. and standing for 12 hours, washing, and drying to obtain a mixed material; S3: mixing the mixed material with petroleum asphalt in a mass ratio of 100:1, and ball milling to obtain a coated material; S4: Under a nitrogen atmosphere, the coated material was heated to 300°C at a rate of 2°C / min and kept at that temperature for 2h to obtain an intermediate product; S5: Under a nitrogen atmosphere, the intermediate product was heated to 1700°C at a rate of 2°C / min and carbonized for 1 h to obtain a biomass-based hard carbon negative electrode material.
[0037] Example 4 This embodiment provides a method for preparing a biomass-based hard carbon negative electrode material, comprising the following steps: S1: crushing the straw residue, sieving it, and obtaining a powder with a particle size of 5-10 μm; mixing the powder, a ash remover and water in a mass ratio of 150:1:100, stirring evenly, and obtaining a mixed solution; wherein the ash remover comprises tetrasodium hydroxyethylidene diphosphonate and polyhydroxyacrylic acid, and the mass ratio of tetrasodium hydroxyethylidene diphosphonate to polyhydroxyacrylic acid is 1:10; S2: heating the mixed solution to 80° C. and standing for 12 hours, washing, and drying to obtain a mixed material; S3: mixing the mixed material with petroleum asphalt in a mass ratio of 200:1, and ball milling to obtain a coated material; S4: Under a nitrogen atmosphere, the coated material was heated to 300°C at a rate of 2°C / min and kept at that temperature for 2h to obtain an intermediate product; S5: Under a nitrogen atmosphere, the intermediate product was heated to 1500°C at a rate of 2°C / min and carbonized for 3 h to obtain a biomass-based hard carbon negative electrode material.
[0038] Example 5 This embodiment provides a method for preparing a biomass-based hard carbon negative electrode material, comprising the following steps: S1: crushing and sieving bagasse to obtain a powder with a particle size of 5-10 μm; mixing the powder, a ash remover and water in a mass ratio of 250:1:100, stirring evenly to obtain a mixed solution; wherein the ash remover comprises tetrasodium hydroxyethylidene diphosphonate and polyhydroxyacrylic acid, and the mass ratio of tetrasodium hydroxyethylidene diphosphonate to polyhydroxyacrylic acid is 3:1; S2: heating the mixed solution to 80° C. and standing for 12 hours, washing, and drying to obtain a mixed material; S3: mixing the mixed material with petroleum asphalt in a mass ratio of 50:1, and ball milling to obtain a coated material; S4: Under a nitrogen atmosphere, the coated material was heated to 300°C at a rate of 2°C / min and kept at that temperature for 2h to obtain an intermediate product; S5: Under a nitrogen atmosphere, the intermediate product was heated to 1500°C at a rate of 2°C / min and carbonized for 3 h to obtain a biomass-based hard carbon negative electrode material.
[0039] Example 6 This embodiment provides a method for preparing a biomass-based hard carbon negative electrode material, comprising the following steps: S1: crushing and sieving bagasse to obtain a powder with a particle size of 5-10 μm; mixing the powder, a ash remover and water in a mass ratio of 250:1:100, stirring evenly to obtain a mixed solution; wherein the ash remover comprises tetrasodium hydroxyethylidene diphosphonate and polyhydroxyacrylic acid, and the mass ratio of tetrasodium hydroxyethylidene diphosphonate to polyhydroxyacrylic acid is 5:1; S2: heating the mixed solution to 80° C. and standing for 12 hours, washing, and drying to obtain a mixed material; S3: mixing the mixed material with petroleum asphalt in a mass ratio of 50:1, and ball milling to obtain a coated material; S4: Under a nitrogen atmosphere, the coated material was heated to 300°C at a rate of 2°C / min and kept at that temperature for 2h to obtain an intermediate product; S5: Under a nitrogen atmosphere, the intermediate product was heated to 1500°C at a rate of 2°C / min and carbonized for 3 h to obtain a biomass-based hard carbon negative electrode material.
[0040] All comparative examples in the present invention are compared with Example 1.
[0041] Comparative Example 1 This comparative example provides a method for preparing a biomass-based hard carbon negative electrode material, comprising the following steps: S1: crushing and sieving bagasse to obtain a powder with a particle size of 5-10 μm; mixing the powder with water at a mass ratio of 250:100, stirring evenly, to obtain a mixed solution; wherein the deashing agent comprises tetrasodium hydroxyethylidene diphosphonate and polyhydroxyacrylic acid, and the mass ratio of tetrasodium hydroxyethylidene diphosphonate to polyhydroxyacrylic acid is 1:1; S2: heating the mixed solution to 80° C. and standing for 12 hours, washing, and drying to obtain a mixed material; S3: mixing the mixed material with petroleum asphalt in a mass ratio of 50:1, and ball milling to obtain a coated material; S4: Under a nitrogen atmosphere, the coated material was heated to 300°C at a rate of 2°C / min and kept at that temperature for 2h to obtain an intermediate product; S5: Under a nitrogen atmosphere, the intermediate product was heated to 1500°C at a rate of 2°C / min and carbonized for 3 h to obtain a biomass-based hard carbon negative electrode material.
[0042] Comparative Example 2 This comparative example provides a method for preparing a biomass-based hard carbon negative electrode material, comprising the following steps: S1: crushing bagasse and sieving to obtain a powder with a particle size of 5-10 μm; mixing the powder, a ash remover and water at a mass ratio of 250:1:100, stirring evenly to obtain a mixed solution; wherein the ash remover is tetrasodium hydroxyethylidene diphosphonate; S2: heating the mixed solution to 80° C. and standing for 12 hours, washing, and drying to obtain a mixed material; S3: mixing the mixed material with petroleum asphalt in a mass ratio of 50:1, and ball milling to obtain a coated material; S4: Under a nitrogen atmosphere, the coated material was heated to 300°C at a rate of 2°C / min and kept at that temperature for 2h to obtain an intermediate product; S5: Under a nitrogen atmosphere, the intermediate product was heated to 1500°C at a rate of 2°C / min and carbonized for 3 h to obtain a biomass-based hard carbon negative electrode material.
[0043] Comparative Example 3 This comparative example provides a method for preparing a biomass-based hard carbon negative electrode material, comprising the following steps: S1: crushing sugarcane bagasse, sieving, and obtaining a powder with a particle size of 5-10 μm; mixing the powder, a deashing agent, and water at a mass ratio of 250:1:100, stirring evenly, and obtaining a mixed solution; wherein the deashing agent is polyhydroxy acrylic acid; S2: heating the mixed solution to 80° C. and standing for 12 hours, washing, and drying to obtain a mixed material; S3: mixing the mixed material with petroleum asphalt in a mass ratio of 50:1, and ball milling to obtain a coated material; S4: Under a nitrogen atmosphere, the coated material was heated to 300°C at a rate of 2°C / min and kept at that temperature for 2h to obtain an intermediate product; S5: Under a nitrogen atmosphere, the intermediate product was heated to 1500°C at a rate of 2°C / min and carbonized for 3 h to obtain a biomass-based hard carbon negative electrode material.
[0044] Comparative Example 4 This comparative example provides a method for preparing a biomass-based hard carbon negative electrode material, comprising the following steps: S1: crushing and sieving bagasse to obtain a powder with a particle size of 5-10 μm; mixing the powder, a ash remover and water in a mass ratio of 250:1:100, stirring evenly to obtain a mixed solution; wherein the ash remover comprises tetrasodium hydroxyethylidene diphosphonate and polyhydroxyacrylic acid, and the mass ratio of tetrasodium hydroxyethylidene diphosphonate to polyhydroxyacrylic acid is 1:1; S2: heating the mixed solution to 80° C. and standing for 12 hours, washing, and drying to obtain a mixed material; S3: Under a nitrogen atmosphere, the mixture was heated to 300°C at a rate of 2°C / min and kept at that temperature for 2 h to obtain an intermediate product; S4: Under a nitrogen atmosphere, the intermediate product was heated to 1500°C at a rate of 2°C / min and carbonized for 3 h to obtain a biomass-based hard carbon negative electrode material.
[0045] Comparative Example 5 This comparative example provides a method for preparing a biomass-based hard carbon negative electrode material, comprising the following steps: S1: crushing and sieving bagasse to obtain a powder with a particle size of 5-10 μm; mixing the powder with water at a mass ratio of 250:100, stirring evenly, to obtain a mixed solution; wherein the deashing agent comprises tetrasodium hydroxyethylidene diphosphonate and polyhydroxyacrylic acid, and the mass ratio of tetrasodium hydroxyethylidene diphosphonate to polyhydroxyacrylic acid is 1:1; S2: heating the mixed solution to 80° C. and standing for 12 hours, washing, and drying to obtain a mixed material; S3: mixing the mixed material with petroleum asphalt in a mass ratio of 50:1, and ball milling to obtain a coated material; S4: Under a nitrogen atmosphere, the coated material was heated to 1500°C at a rate of 2°C / min and carbonized for 3h to obtain a biomass-based hard carbon negative electrode material.
[0046] The composite negative electrode materials prepared in each embodiment and comparative example were used as negative electrode active materials, and were uniformly mixed with polyvinylidene fluoride (PVDF) (dissolved in N-methylpyrrolidone) and conductive carbon black in a mass ratio of 90:5:5, coated into an electrode film, and dried in a vacuum drying oven at 120°C for 12 hours. After rolling and punching, a hard carbon negative electrode sheet was obtained; a metal sodium sheet was used as a counter electrode, 1 mol / L NaPF6 (EC-DEC=1:1) was used as an electrolyte, and the hard carbon negative electrode sheets obtained above were assembled into 2430 button batteries in a glove box, and the current size was 0.5 mA / cm 2 , and tested its electrochemical performance. The test results are shown in Table 1: Table 1 It can be seen from the data in Table 1 that the negative electrode materials prepared in the embodiments of the present invention have a maximum capacity of 342 mAh / g, a first coulombic efficiency of 92%, and excellent cycle performance.
[0047] Combined with the data of each comparative example, specifically, the difference between comparative example 1 and embodiment 1 is that no deashing agent is added. Due to the high ash content of the negative electrode material, the specific capacity and the first efficiency of the prepared hard carbon negative electrode material are both low; the difference between comparative example 2 and embodiment 1 is that the deashing agent is a single component of tetrasodium hydroxyethylidene diphosphonate. Due to the uneven removal of the ash content of the negative electrode material, the prepared hard carbon negative electrode material has improved various properties compared with comparative example 1, but due to the poor product consistency, the cycle performance is poor; the difference between comparative example 3 and embodiment 1 is that the deashing agent is a single component of polyhydroxypropyl Oleic acid, due to the incomplete removal of the ash content of the negative electrode material, the performance of the prepared hard carbon negative electrode material is slightly better than that of Example 1, but compared with Example 1, the specific capacity and the first efficiency are both lower; the difference between Example 4 and Example 1 is that the material is not coated with a coating agent, and due to the side reaction between the electrolyte and the negative electrode material during the cycle, the cycle performance of the prepared hard carbon negative electrode material is poor; the difference between Example 5 and Example 1 is that the coated material is directly carbonized at high temperature, and due to the poor pore structure of the negative electrode material, the specific capacity and the first efficiency of the prepared hard carbon negative electrode material are low.
[0048] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A method for preparing a biomass-based hard carbon negative electrode material, characterized in that: The steps include: S1: mixing a biomass raw material, a ash removal agent and a solvent to obtain a mixed solution; S2: After the mixed solution is allowed to stand at 25° C.-120° C., it is washed and dried to obtain a mixed material; S3: coating the mixed material with a coating agent to obtain a coated material; S4: In an inert gas atmosphere, the coated material is kept at 200-400° C. to obtain an intermediate product; S5: In an inert gas atmosphere, the intermediate product is kept at 1200-1700° C. to obtain a biomass-based hard carbon negative electrode material.
2. The method for preparing a biomass-based hard carbon negative electrode material according to claim 1, characterized in that: The biomass raw material is selected from at least one of bagasse, bamboo charcoal, coffee grounds and straw residue.
3. The method for preparing a biomass-based hard carbon negative electrode material according to claim 1, characterized in that: The deashing agent includes an organic phosphonate deashing agent and a polyacrylic acid deashing agent.
4. The method for preparing a biomass-based hard carbon negative electrode material according to claim 3, characterized in that: The organic phosphonate deashing agent is selected from at least one of tetrasodium hydroxyethylene diphosphonate, sodium ethylenediamine tetramethylene phosphate, diethylenetriamine penta (methylene phosphonate), and amine trimethylene phosphate.
5. The method for preparing a biomass-based hard carbon negative electrode material according to claim 3, characterized in that: The polyacrylic acid deashing agent is selected from at least one of hydrolyzed polymaleic anhydride, polyacrylic acid, polyhydroxyacrylic acid, maleic acid acrylic acid copolymer, and polyacrylamide.
6. The method for preparing a biomass-based hard carbon negative electrode material according to claim 3, characterized in that: The mass ratio of the organic phosphonate deashing agent to the polyacrylic acid deashing agent is (100-1): (1-100).
7. The method for preparing a biomass-based hard carbon negative electrode material according to claim 1, characterized in that: The coating agent is selected from at least one of petroleum asphalt, coal asphalt, sucrose, starch, sucrose, fructose, phenolic resin, epoxy resin, polydopamine, polyvinyl pyrrolidone, tannic acid, citric acid, polyvinyl alcohol, polypyrrole, vitamin C, polyethylene glycol, and aniline.
8. The method for preparing a biomass-based hard carbon negative electrode material according to any one of claims 1 to 7, characterized in that: The mass ratio of the biomass raw material to the deashing agent in step S1 is (5-500):1; the mass ratio of the mixed material to the coating agent in step S3 is (50-500):
1.
9. A biomass-based hard carbon negative electrode material, characterized in that: The method is used to prepare the biomass-based hard carbon negative electrode material according to any one of claims 1 to 8.
10. A sodium ion battery, characterized in that: Comprising the biomass-based hard carbon negative electrode material as described in claim 9.
Citation Information
Cited By
Biomass deironing and deliming process based on ultrasonic cavitation and application of biomass deironing and deliming process
CN121490696A